Effect of finger-holding technique on pain and anxiety in patients after Transurethral Resection of the Prostate (TURP): A quasi-experimental study - Novi Yanti S; Fauzi Ashra; Dwi Apriadi; Junios Junios; Yuhendri Putra; Fera Liza (Lentera Perawat, 2026)
Background: Patients undergoing Transurethral Resection of the Prostate frequently experience postoperative pain and anxiety during the early recovery phase. Non-pharmacological nursing interventions may help improve patient comfort and psychological stability during this period. Objective: This study aimed to examine the effect of the finger-holding technique on pain and anxiety among patients after Transurethral Resection of the Prostate. Methods: A quantitative quasi-experimental study with a nonequivalent control group design was conducted at Siti Fatimah Hospital Palembang from July to September 2025. Thirty-four postoperative patients were recruited using purposive sampling and divided into an intervention group (n=17) and a control group (n=17). The intervention group received the finger-holding relaxation technique twice daily for three days in addition to standard postoperative care, while the control group received standard care only. Pain intensity was measured using the Numeric Rating Scale, and anxiety levels were assessed using the Generalized Anxiety Disorder-7 scale. Data were analyzed using descriptive statistics and comparative tests with a significance level of p<0.05. Results: Both groups experienced reductions in pain and anxiety after the treatment period. The intervention group demonstrated a greater reduction in mean pain score from 6.47 to 2.06 compared with the control group, which decreased from 7.00 to 4.76. Anxiety scores in the intervention group decreased from 11.88 to 4.24, whereas the control group decreased from 11.53 to 7.18. Statistical analysis showed significant improvements in both groups, with a stronger effect observed in the intervention group. Conclusion: The finger-holding technique effectively reduces pain and anxiety in patients after Transurethral Resection of the Prostate and may serve as a simple complementary nursing intervention to improve postoperative comfort.